2005
DOI: 10.1037/0735-7044.119.2.455
|View full text |Cite
|
Sign up to set email alerts
|

(±)3,4-Methylenedioxymethamphetamine, d-Amphetamine, and Cocaine Impair Delayed Matching-to-Sample Performance by an Increase in Susceptibility to Proactive Interference.

Abstract: This study compared the effects of (+/-)3,4-methylenedioxymethamphetamine, d-amphetamine, and cocaine on performance of rats in a delayed matching-to-sample procedure using a variety of indices of performance to determine the mechanism by which working memory task impairments arise. All 3 drugs produced an overall delay-independent decrease in accuracy rather than a delay-dependent increase in the rate of forgetting. This impairment arose as a result of current-trial choice responses being progressively more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
89
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(101 citation statements)
references
References 56 publications
12
89
0
Order By: Relevance
“…The rapid decline in log d over delay intervals lasting several seconds in the present study is consistent with numerous DMTS studies in pigeons (for a recent review see White, 2013), rats (Harper et al, 2005), nonhuman primates (Wright, Urcuioli, and Sands, 1986), and humans (Williams, Johnston, and Saunders, 2006). Furthermore, log d showed a consistent delay interval-dependent decrease across repeated tests and typically decreased to near chance levels within 10 seconds.…”
Section: Discussionsupporting
confidence: 91%
“…The rapid decline in log d over delay intervals lasting several seconds in the present study is consistent with numerous DMTS studies in pigeons (for a recent review see White, 2013), rats (Harper et al, 2005), nonhuman primates (Wright, Urcuioli, and Sands, 1986), and humans (Williams, Johnston, and Saunders, 2006). Furthermore, log d showed a consistent delay interval-dependent decrease across repeated tests and typically decreased to near chance levels within 10 seconds.…”
Section: Discussionsupporting
confidence: 91%
“…Rats showed impairment on a delayed matching to sample task at low doses of 0.6 and 1.0 mg/kg amphetamine, i.p. (Harper et al 2005). At these doses, the responses rats gave for a given trial were greatly influenced by their responses from the preceding trial.…”
Section: Discussionmentioning
confidence: 97%
“…The conclusions of the above studies were that acute MDMA results in working memory impairments. However, it has been argued that these findings do not involve working memory effects, but rather reflect disruptions of reference memory involving the rules or strategies associated with a given task (Harper et al, 2005; 2006; Kay et al, 2010). As an illustration, Kay et al (2010) used a version of the radial arm maze designed to separate working and reference memory and found that MDMA had no effect on the working memory task (arms were always baited for one visit), but impaired the reference memory task (arms that were never baited throughout the experiment).…”
Section: Discussionmentioning
confidence: 99%